Pembelajaran Model Pendidikan Anak dalam Al-Qur’an terhadap Kisah Nabi Ibrahim - Dwi Noviatul Zahra; Nurul Aisyah (QuranicEdu: Journal of Islamic Education, 2022)
The purpose of this research was to create a children's learning model based on the story of the prophet Ibrahim and his family in the Koran. The verse was then analyzed using a thematic analysis model. Based on the research results, it showed that the family learning model taught by the prophet Ibrahim to his children used prenatal and postnatal learning models. Prenatal learning was the awareness of parents in providing education to their children since their children were still in the womb or long before their children were born, such as in choosing a partner which was included as an effort to educate children. In contrast, postnatal learning was the awareness of parents in educating their children after birth.